2011
DOI: 10.11564/25-1-266
|View full text |Cite
|
Sign up to set email alerts
|

Does correct knowledge about HIV and AIDS lead to safer sexual behaviour? The case of young people in Botswana

Abstract: This article investigates the extent to which acquired correct knowledge about HIV and AIDS prevention and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
6
1
Order By: Relevance
“…Young people may be knowledgeable about the importance of using a condom consistently or practice safe sex. Unsafe sexual behaviour may be practiced by young people because of circumstances that dictate unsafe sexual behaviour [41]. This dictates that young people should develop life skills to make informed choices about safe sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young people may be knowledgeable about the importance of using a condom consistently or practice safe sex. Unsafe sexual behaviour may be practiced by young people because of circumstances that dictate unsafe sexual behaviour [41]. This dictates that young people should develop life skills to make informed choices about safe sex.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on condom use in Botswana focused on awareness, knowledge and practices in relation to condom use among university students [34] [35] [36] and attitudes towards condom use for prevention of HIV infection in Botswana [37]. In some studies carried out in Botswana, the temporal relationships between predictors and condom use have been obscured by the inclusion of condom use variables in the determination of risky sexual behaviour indices [38] [39] [40] [41]. The need to inform sexual and reproductive interventions on factors associated with condom use among adolescents is thus critical as little is known on what influences adolescent condom use in Botswana.…”
Section: E Ngomementioning
confidence: 99%
“…Given the progressive innovations and advancements in ICTs and increased access to online media and the rising levels of media literacy among young people nowadays, with higher programme appeals and the growing popularity of the local Kannywood movies, or Hausa home video in Northern Nigeria (Larkin, 2004), there appears a case for the reassessment of adolescents' ICT-media exposure particularly as it affects their HIV/ AIDS KAP. Several studies in the past investigated relationships among HIV/AIDS knowledge, attitude and practice (KAP) variables (e.g., Tung et al, 2008;Bekalu & Eggrmon, 2013;Letamo, 2011: Li et al, 2009Moore, 2008) and found relationships among these variables. These studies suggested correlations among the HIV/AIDS KAP variables and that respondents' major sources of information about HIV/AIDS are the media, especially online media.…”
Section: Ict-media Exposure and Knowledge Attitude And Practice On Hmentioning
confidence: 99%
“…In Zimbabwe, as in many other southern African states under patriarchal conditions, where cultural norms and turbulent social malaise have effects for gender relations, understanding and addressing adolescent sexuality is of vital importance in light of young women's increased vulnerability to early childbearing, HIV, and gender/sexual violence (Bhana, 2018;Masvawure, 2010). Understanding how adolescents make meaning of sexuality is urgent, at a time when studies suggest that adolescent awareness of and information about sexually risky practices does not necessarily translate into safe sex (Bruce et al, 2011;Letamo, 2011;Nubed & Akoachere, 2016). The national HIV prevalence rate in Zimbabwe is 14% in both urban and rural parts of the country though prevalence is higher among women (17%) compared to men (14%) (Zimbabwe National Statistics Agency [ZIMSTAT], 2015).…”
Section: Introductionmentioning
confidence: 99%